Qualitative research in sport and physical activity - Jones, Ian 1970-
Designed especially for students in sport and physical activity, this book provides a detailed guide to planning, undertaking, and writing up qualitative research. It is a coherent and accessible guide through the research process, using numerous examples to bring research alive
Keywords: Sports -- Research -- Methodology; Qualitative research; Sport; Qualitative Methode